Features of student training from discipline "obstetrics and gynecology" under conditions of war state - Krut, Yu. Ya.; Siusiuka, V. H.; Serhienko, M. Yu.; Pavluchenko, M. I.; Shevchenko, A. O.; Круть, Юрій Якович; Сюсюка, Володимир Григорович; Сергієнко, Марина Юріївна; Павлюченко, Михайло Іванович; Шевченко, Анна Олександрівна (My University, 2023)
Coronavirus pandemic has forced to expand the possibilities of distance learning (DL) at the Zaporizhzhia State Medical and Pharmacological University (ZSMPU), which was previously used for advanced training courses. Access to Microsoft Office 365 distance learning service and Microsoft Teams software has been organized for all teachers and students.